Relationship Between Oral Language Anxiety and Students’ Arabic Language Learning Outcomes in Malaysian Secondary Schools - Zawawi Ismail; Nurwaina Rasit; Triyo Supriyatno (Universitas Negeri Makassar, 2023)
Anxiety is an affective factor that plays an important role in affecting the mastery and achievement of language learning. This study aims to examine the level of oral language anxiety and its relationship with learning outcomes among religious secondary school students in Malaysia. The questionnaire was distributed to 500 form four students from 20 religious secondary schools. Findings show that the levels of oral language anxiety are moderately high level with values (Min = 3.48; SP = 0.64). The significant relationship between student learning outcomes and listening anxiety skills (r = -.121, p <.05) and speaking anxiety (r = -.154, p <. 05) at a significance level of 0.01. This study suggests that teachers should always be sensitive to the psychological needs of students by always providing motivation, and encouragement and using effective teaching methods to overcome the anxiety of learning Arabic.